The Influence of Independence, Competence and Time Budget Pressure on Audit Quality with Auditor Ethics as a Moderating Variable at Big Ten Public Accounting Firms - Fajar Mardika (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya (UPR), 2024)
This study aims to determine